MICROWAVE ASSISTED SYNTHESIS AND STRUCTURAL CHARACTERISATION OF NICOTINIC ACID AND NITRITO–ΚO MIXED LIGAND COMPLEXES: Pharmaceutical Science-Chemistry - SURENDRA DILIP, C.; JOTHI VENKATACHALAM, K.; PAUL RAJ, A.; RAMACHANDRAMOORTHY, T. (International Journal of Life Science and Pharma Research, 2011)
The mixed ligand complexes were prepared using nicotinic acid and nitrto-κO ions as ligands with CrIII, CoII, NiII, CuII and CdII ions. The complexes are identified as neutral, non electrolytes and distorted octahedral in structure for the CrIII, CoII and NiII complexes, tetragonal for the CuII and pseudo tetrahedral for the CdII complexes. These have been characterized by using elemental analysis, IR, magnetic susceptibility, conductance measurements and electronic spectral studies. The shifts of the ν(C=N) (azomethine) and ν (C=O) frequencies are monitored in order to find out the donor sites of the ligands. The nicotinic acid is neutral, monodentate and coordinates through the pyridine ring nitrogen. The elemental and spectral analyses interpret the geometry for these complexes.